2016
DOI: 10.1177/1687814016652564
|View full text |Cite
|
Sign up to set email alerts
|

Vibration reduction in beam bridge under moving loads using nonlinear smooth and discontinuous oscillator

Abstract: The coupled system of smooth and discontinuous absorber and beam bridge under moving loads is constructed in order to detect the effectiveness of smooth and discontinuous absorber. It is worth pointing out that the coupled system contains an irrational restoring force which is a barrier for conventional nonlinear techniques. Hence, the harmonic balance method and Fourier expansion are used to obtain the approximate solutions of the system. The first and the second kind of generalized complete elliptic integral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…According to equations (1) and (2), the relationship between the spring's deformation δ and the shear strain c is…”
Section: Relationship Between the Elongation Of Sma Spring Andmentioning
confidence: 99%
See 1 more Smart Citation
“…According to equations (1) and (2), the relationship between the spring's deformation δ and the shear strain c is…”
Section: Relationship Between the Elongation Of Sma Spring Andmentioning
confidence: 99%
“…Due to its geometric nonlinearity, the restoring force yielded the irrational nonlinear form, which made its frequency vary depending on the smoothness parameter α. In recent years, the applications of SD oscillator for the vibration reduction have been studied [2,3], which showed that the desired effect of the vibration reduction can be achieved by adjusting the smooth parameter α. However, in these papers, how to change α to realize the frequency conversion is barely mentioned.…”
Section: Introductionmentioning
confidence: 99%
“…As is given in Tian et al, 20 SD oscillator is an example of a conservative system whose natural frequency can be changed depending on the parameter a = l 0 =l (see Figure 1). In fact, from Figure 1, we know that if the springs of SD absorber are vertical and a = 0, SD absorber can be regarded as a linear absorber (TMD).…”
Section: Vehicle-bridge-sd Absorber Coupled Systemmentioning
confidence: 99%
“…In a complicated real system, frequency often shifts from one mode to another, which involves a versatile dynamic absorber which can lead itself to linear dynamic dampers or nonlinear one to meet reduction demands. As is given in Tian et al, 20 SD oscillator is an example of a conservative system whose natural frequency can be changed depending on the parameter a = l 0 =l (see Figure 1). In fact, from Figure 1, we know that if the springs of SD absorber are vertical and a = 0, SD absorber can be regarded as a linear absorber (TMD).…”
Section: Vehicle-bridge-sd Absorber Coupled Systemmentioning
confidence: 99%
See 1 more Smart Citation